2023
DOI: 10.1155/2023/4199052
|View full text |Cite
|
Sign up to set email alerts
|

AT7867 Inhibits the Growth of Colorectal Cancer Stem-Like Cells and Stemness by Regulating the Stem Cell Maintenance Factor Ascl2 and Akt Signaling

Abstract: Cancer stem cells (CSCs) are the core factors leading to recurrence, insensitivity to radiotherapy and chemotherapy, and immunotherapy resistance in patients with colorectal cancer. AT7867, a potent oral AKT inhibitor, was found to have antitumor activity in colorectal cancer; however, the effect on colorectal cancer stem cells is still unclear. This study was conducted to clarify the molecular mechanism underlying the CSC growth inhibitory effects of AT7867. We cultured colorectal cancer cells (CRCs) in a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This 50-gene signature was notable for the presence of several unique CSC-associated genes, such as, AGR2 85 , ASCL2 86,87 , ALDH3A1 88 , and TM4SF1 89,90 , that were not parts of CSC signatures identified by machine-learning ( Figure 4C-F ). The 50 genes were enriched for pathways that are known to augment CSC survival 9194 , e.g., PTK6-dependent JAK/STAT signaling, numerous growth factor receptor and non-receptor TK and the Hippo/YAP pathways and loss of TGFβ signaling ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This 50-gene signature was notable for the presence of several unique CSC-associated genes, such as, AGR2 85 , ASCL2 86,87 , ALDH3A1 88 , and TM4SF1 89,90 , that were not parts of CSC signatures identified by machine-learning ( Figure 4C-F ). The 50 genes were enriched for pathways that are known to augment CSC survival 9194 , e.g., PTK6-dependent JAK/STAT signaling, numerous growth factor receptor and non-receptor TK and the Hippo/YAP pathways and loss of TGFβ signaling ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…We used this 50-gene signature as a computational tool to track the changes along the stemness→differentiation axis that occurs due to reinstatement of CDX2 and found that PF suppressed these genes (Figure 5B; see Supplemental Information 6) to levels seen in healthy PDOs and CDX2-high CRC PDOs (Figure S8A-B). This 50-gene signature was notable for the presence of several unique CSC-associated genes, such as, AGR2 42 , ASCL2 43,44 , ALDH3A1 45 , and TM4SF1 46,47 , that were not parts of CSC signatures identified by machine-learning (Figure 4C-F). The 50 genes were enriched for pathways that are known to augment CSC survival [48][49][50][51] , e.g., PTK6-dependent JAK/STAT signaling, numerous growth factor receptor and non-receptor TK and the Hippo/YAP pathways and loss of TGFβ signaling (Figure 5C).…”
Section: A Molecular Signature Of Therapeutic Response and Selectivitymentioning
confidence: 99%
“…AT7867 is a potent AKT and p70 S6 kinase inhibitor used to slow the progression of tumor growth by inducing G2/M phase arrest and cell apoptosis in cancer stem cells 50,51 . AT7867 has also been described to induce the proliferation of PDX1 + cells; furthermore, Kimura et al described that the increased cell density as a result of AT7867 mediated proliferation triggered the upregulation of PDX1 and NKX6.1in PP cells 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Their study revealed significant inhibitory effects of AT7867 on CSC proliferation and stemness attributes, offering promising therapeutic potential. By elucidating the mechanism involving the downregulation of Ascl2 and interference with the Akt signaling pathway, they proposed a compelling strategy for targeting CSCs in CRC treatment [97].…”
Section: Ccsc and Drug Resistancementioning
confidence: 99%